Pendalaman Alkitab Berbasis Mazmur 32: Dari Pengakuan Dosa Menuju Pemulihan Sukacita bagi Jemaat GKB Bahtera Hayat Semarang - Pujiati Pujiati; Ragil Kristiawan (Journal Of Social Empowerment Publications, 2026)
This Community Service Program presents a spiritual intervention through "Bible Study Based on Psalm 32" for the congregation of GKB Bahtera Hayat Semarang. The context of modern urban life often gives rise to psychospiritual challenges in the form of unacknowledged guilt, leading to an identity crisis and spiritual alienation. This program was designed to address these issues by offering a comprehensive exposition of Psalm 32, which maps the transformative journey from confession of sin to the restoration of joy. The implementation methods included in-depth library research, interactive lectures, and practical spiritual exercises. The discussion results indicate that the literary structure and theological themes of Psalm 32 encompassing honest confession, the assurance of forgiveness, and the promise of divine protection successfully provided an applicable framework. This program concludes that a Bible study model based on Psalm 32 is an effective and contextual model for restoring the spiritual joy of urban congregations, while also contributing to the formation of a community grounded in grace and openness.